P2-S1.08 Dual contraceptive use among adolescents and young adults: correlates and implications for condom use and STI outcomes. (10th July 2011) - Hood, J; Hogben, M; Chartier, M; Bolan, G; Bauer, H
Abstract : Background: Simultaneous use of condoms and other contraceptive methods ("dual use") provides the maximum protection against unintended pregnancies and sexually transmitted disease (STD). Some studies show condom use wanes among dual users, thus potentially increasing STD risk. The purpose of this study is to (1) demonstrate how the composition of comparison groups influence conclusions regarding condom use and STD risk among hormonal contraceptive (HC) users and (2) assess the correlates of dual use. Methods: A convenience sample of youth ages 12–25 years (n=1450) were screened for chlamydia and gonorrhoea at non-clinical sites in high morbidity neighbourhoods of two California counties in 2002–2003. Gender-specific ORs for three outcomes (condom use consistency, condom use at last sex, and positive STD result) were calculated for three separate comparisons: (1) HC vs non-HC users, (2) HC vs condom only users, and (3) dual vs condom only users. Multivariate logistic regression models were constructed to assess the correlates of dual use. Results: Each of the three comparisons led to different conclusions (see Abstract P1-S1.08 table 1 ). For our broadest comparison (HC vs non-HC users), female HC users were less likely to screen positive for an STD. However, males who reported that their partners used HC were less likely to report frequent condom use. In the second comparison (HC vs condom only), condom use at last sex and frequent condom use was significantly less common among HC users than condom only users. In the final comparison, dual users did not differ from condom-only users. Sex, age, race, and relationship tenure were significant correlates of dual use. Females were more likely to report dual use [aOR=1.6 (1.1 to 2.3)], as were older adolescents (16–18 years) vs young adolescents (12–15 years) [aOR=2.1 (1.3 to 3.3)]. Relative to Whites, African Americans and Hispanics were less likely to report dual use [AA: aOR=0.4 (0.2 to 0.6); Hisp: aOR=0.5 (0.3 to 0.7)]. Respondents in longer-term relationships were more likely to report dual use than respondents in new relationships. Discussion: Conclusions on whether condom use wanes among dual users may depend on the composition of groups compared. Future investigation of condom use among HC users should address this potential source of bias. If interpreted alongside each sub-groups' risk patterns for STD and unplanned pregnancy, the correlates of dual use can inform dual use interventions.